Visible light-promoted transition metal-free direct C3-carbamoylation of 2H-Indazoles - Ma, Chunhua; Shang, Linchun; Zhao, Hanying; He, Xing; Lv, Qiyan; Zhang, Dandan; Jiang, Yuqin (Frontiers in Chemistry, 2022)
We reported a general transition metal-free transformation to access C3-carbamoylated 2H-indazoles via visible light-induced oxidative decarboxylation coupling, in the presence of oxamic acids as the coupling sources, 4CzIPN as the photocatalyst, and Cs2CO3 as the base. The great application potential of this mild condition is highlighted by the late-stage modification of drugs, N-terminal modification of peptides, and the good antitumor activity of the novel desired product.